2013
DOI: 10.1308/003588412x13373405387735
|View full text |Cite
|
Sign up to set email alerts
|

Congenital lung malformations: an ongoing controversy

Abstract: IntroductionCongenital lung malformations are rare lesions that are most commonly diagnosed antenatally. Management of such lesions, particularly those that are asymptomatic, remains controversial. We undertook a survey to ascertain current practice of surgeons in the UK and Ireland.MethodsAll consultant members of the British Association of Paediatric Surgeons were asked to complete a survey on congenital lung malformations with respect to antenatal management, symptomatic and asymptomatic lesions, and operat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 11 publications
3
36
0
Order By: Relevance
“…Twenty percent of surgeons reported never resecting an asymptomatic lesion, whereas 24% would always do so. 15 In our experience, excising asymptomatic lesions is safe with minimal complications. Single-lung ventilation in combination with thoracoscopy provides excellent vision.…”
Section: Discussionmentioning
confidence: 73%
“…Twenty percent of surgeons reported never resecting an asymptomatic lesion, whereas 24% would always do so. 15 In our experience, excising asymptomatic lesions is safe with minimal complications. Single-lung ventilation in combination with thoracoscopy provides excellent vision.…”
Section: Discussionmentioning
confidence: 73%
“…Kotecha [2] also recommended medical observation for asymptomatic children with congenital cystic adenomatous malformations (CCAM) and only promoted surgery for children who were identified as being at risk of developing future symptoms. Peters et al [9] reported that 20% of surgeons in the UK and Ireland never resect an asymptomatic lesion. Ng et al [1] reported that 5% of asymptomatic infants (3/60) developed symptoms associated with CCAM after a median follow-up period of 5 years.…”
Section: Discussionmentioning
confidence: 99%
“…While it is widely accepted that CLMs causing hydrops, pneumothorax, or recurrent pneumonia require intervention, the optimal management of asymptomatic lesions is a divisive topic. The main argument in favor of early resection is to decrease the later risk of infection and malignancy within the lesions, risks that some contend are overstated . Thompson et al reported retrospectively on 159 newborns with prenatally‐detected CLMs, 18% of whom were symptomatic and underwent lobectomy in the neonatal period.…”
Section: Rare Lung Diseasesmentioning
confidence: 99%
“…The main argument in favor of early resection is to decrease the later risk of infection and malignancy within the lesions, risks that some contend are overstated. [6][7][8] Thompson et al 9 reported retrospectively on 159 newborns with prenatally-detected CLMs, 18% of whom were symptomatic and underwent lobectomy in the neonatal period. Another 13% became symptomatic with infection and had later resection.…”
Section: Identification Of Congenital Lung Malformations (Clms) Hasmentioning
confidence: 99%